2022
DOI: 10.1002/iub.2669
|View full text |Cite
|
Sign up to set email alerts
|

Steviol glycosides affect functional properties and macromolecular expression of breast cancer cells

Abstract: Steviol glycosides, the active sweet components of stevia plant, have been recently found to possess a number of therapeutic properties, including some recorded anticancer ones against various cancer cell types (breast, ovarian, cervical, pancreatic, and colon cancer). Our aim was to investigate this anticancer potential on the two most commonly used breast cancer cell lines which differ in the phenotype and estrogen receptor (ER) status: the low metastatic, ERα+ MCF-7 and the highly metastatic, ERαÀ/ERβ+ MDA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that stevioside extract improves neural cell viability and proliferation [32]. Interestingly, stevioside also has the potential to be an anticancer drug because it induces a dose-dependent decline in the cell viability of breast cancer cells but promotes the proliferation of successfully surviving cells [33]. EdU is a thymidine analog that is incorporated into cells only during the S-phase of the cell cycle and thus can be used to assess cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that stevioside extract improves neural cell viability and proliferation [32]. Interestingly, stevioside also has the potential to be an anticancer drug because it induces a dose-dependent decline in the cell viability of breast cancer cells but promotes the proliferation of successfully surviving cells [33]. EdU is a thymidine analog that is incorporated into cells only during the S-phase of the cell cycle and thus can be used to assess cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Steviol inhibited DNA synthesis and induced mitochondrial apoptosis [ 73 ]. In vitro analysis also showed potential activity of steviol glycosides against breast cancer cells [ 74 ]. Furthermore, steviol inhibited human gastrointestinal cancer cell growth through caspase-3 activation and mitochondrial apoptotic pathway triggering, and it increased the Bax/Bcl-2 ratio and stimulated p21 and p53 expression.…”
Section: Pharmacological Properties Of Steviol Glycosidesmentioning
confidence: 99%